Acute Effect of Robotic Therapy (G-EO System™) on the Lower Limb Temperature Distribution of a Patient with Stroke Sequelae - Fábio Marcon Alfieri; Caren da Silva Dias; Artur Cesar Aquino dos Santos; Linamara Rizzo Battistella (Case Reports in Neurological Medicine)
Robotic therapy has been gaining prominence in poststroke rehabilitation programs. An example of these devices is the G-EO System™, which simulates gait as well as other more complexes standards of gait such as the steps on stairs. However, to the best of our knowledge, there are no studies that apply thermography as a tool to evaluate stroke patients who undertook rehabilitation programs with the aid of robotic devices. The patient IWPS undergoes sequelae of hemorrhagic stroke for 19 months and consequently hemiplegia, had scores of 93 points in the Fugl-Meyer scale, is undertaking a physical rehabilitation program for six months, has no complaints of discomfort due to thermic sensitivity imbalances between the plegic and the contralateral sides, and voluntarily reports that he realizes functionality improvements especially, according to his perception, due to the aid of the robotic therapy in his gait training with the G-EO System™. The thermographic images were captured by an infrared sensor FLIR T650SC. By analyzing the temperature differences between both hemispheres of the body, before, immediately after, and 30 minutes after a robotic therapy for gait training, we observed that the values firstly increased immediately after the training, but after the 30-minute rest an important thermoregulation was achieved.